Changes in mindfulness facets in a dialectical behaviour therapy skills training group program for borderline personality disorder. Issue 6 (23rd January 2019) - Mitchell, Roberta; Roberts, Rachel; Bartsch, Dianna; Sullivan, Thomas
Abstract: Objective: We examined the relationship between mindfulness skills acquisition and symptom reduction. Method: Participants were adults ( n  = 35) with a diagnosis of borderline personality disorder (BPD) who completed a 20‐week dialectical behaviour therapy (DBT) skills training group program in a community mental health setting. We used the Five Facet Mindfulness Questionnaire, which measures five dimensions of mindfulness: observing, describing, acting with awareness, nonjudging of inner experience, and nonreactivity to inner experience. Results: Linear mixed model results suggested that increases in some mindfulness facets, especially in acting with awareness and nonjudging of inner experience were more strongly related to changes during treatment including reductions in BPD symptomology, depression, and distress with increases in nonjudging also predicting a reduction in the hospital use. Conclusions: These results suggest the usefulness of emphasising mindfulness skills that develop awareness and encourage a nonjudgmental stance.